2015
DOI: 10.1177/0731684415588938
|View full text |Cite
|
Sign up to set email alerts
|

Natural fiber reinforced polyester composites: A literature review

Abstract: Many composite products are made of thermosetting polymers reinforced with synthetic fibers. Despite the high mechanical properties associated with these fibers they are heavy and expensive compared with natural fibers. The use of natural plant fibres, combinations of natural and synthetic fibers, and wood furnish as reinforcement in polyester matrix for making low cost engineering materials has generated much interest recently. Natural fibers with good specific stiffness and strength, low density, low embodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 47 publications
0
31
0
4
Order By: Relevance
“…Other major jute-and kenaf-growing countries are China, Thailand, Myanmar, Indonesia, Brazil, and Nepal. Africa and the Indo-Myanmar region are the primary and secondary centers of origin, respectively, for jute, while the Indo-Myanmar region including South China is considered the center of origin of jute [68][69][70]. Some major exporters of jute fibres along their annual yields per tons are presented in Figure 1.…”
Section: Habitat Growth and Morphology Of Jutementioning
confidence: 99%
“…Other major jute-and kenaf-growing countries are China, Thailand, Myanmar, Indonesia, Brazil, and Nepal. Africa and the Indo-Myanmar region are the primary and secondary centers of origin, respectively, for jute, while the Indo-Myanmar region including South China is considered the center of origin of jute [68][69][70]. Some major exporters of jute fibres along their annual yields per tons are presented in Figure 1.…”
Section: Habitat Growth and Morphology Of Jutementioning
confidence: 99%
“…All these characteristics of flax make it a potential candidate to grow in metal contaminated soils and it can accumulate metal in the order of root > leaves stem > seed > fiber. Thus, flax can be used for phytoremediation and can provide 100% utilizable raw material which have no harmful residue as well as fully biodegradable waste [64,70,71].…”
Section: Plant Selection Considerationsmentioning
confidence: 99%
“…They proved that flax could tolerate up to 400 mg kg −1 Cu while further increments of metal caused a significant reduction in plant growth and biomass. They also determined Cu used the digestion method at different stages of the plant growth, i.e., 35,70,105, and 140 days after sowing (DAS). Their results also suggested that in the early stage of the life cycle of the plant, Cu tended to accumulate in the roots and was transported to the shoots at the last stage of the plant life cycle.…”
Section: Studies Related To Phytoremediation Of the Flax Plantmentioning
confidence: 99%
“…Several natural reinforcements can be found in literature, including flax, hemp, jute, sisal, cotton, silk, and others . Among these classes of materials, hemp‐reinforced polymeric composites are especially suitable to be applied in industrial design because of their unique mechanical and physical properties …”
Section: Introductionmentioning
confidence: 99%